Survival problems of archaeophytes in the Polish flora - Zając, Maria; Zając, Adam (Biodiversity: Research and Conservation, 2015)
These considerations have been based on the updated list of archaeophytes appearing in Poland. The extent of endangerment has been assessed for particular species according to the updated IUCN classification. Non-threatened and invasive species have also been taken into consideration. A number of quite fundamental changes have been made to the classification, as compared to the publication of Zając et al. of 2009.